(untitled) (Indian Journal of Public Health Research & Development, 2021)
The present study was conducted to determine the changes occurs in hemodynamic variables of (HR, LVSD, LVESD, Stroke volume, Cardiac output) at different training phases of periodization in athletic events such as, middle distance and long-distance running between the male and female novice athletes in athletic training center at maychew, Ethiopia. Materials and Method: In this qazi-experimental study, 18 athletes selected from different phases of training at maychew athletic training center in Ethiopia. The novice athletes of male and female were selected by their performance in the regional wise, as they are novice athletes in the training center they used to go for more than a year training however the researcher wanted to know the hemodynamic parameters changes occurs before the athletes used to engage in specific period of training. To analyze the hemodynamic parameter the subjects were taken to the comprehensive specialized regional hospital then, "Echocardiography was performed by VIVID E-19(General Electric) undertaken using a 2.5MHz probe "are used to calculate several hemodynamic parameters the values of hemodynamic parameters were recorded at intervals. The recorded data were analyzed by SPSS 21 software, using independent t-test, it is concluded that while comparing the male and female novice athletes male athletes are dominating in longdistance then female athletes are dominating in middle distance running events.